65‐4: Investigation on Blue Quantum‐Dot Light‐Emitting Diode with Positive Aging Treatment. Issue 1 (28th June 2021) - Lin, Bo-Yen; Chen, Chia-Hsun; Ding, Wen-Cheng; Kuo, Ya-Pei; Chen, Peng-Yu; Lu, Hsueh-Hsing; Lee, Chun-Yu; Chiu, Tien-Lung; Haw Lee, Jiun-
Abstract : We have demonstrated a high efficiency blue quantum‐dot light‐emitting diode (QLED) with positive aging treatment. While device was statically stored 602 hrs, the external quantum efficiency (EQE) of QLED increased from 4.8% to 7.8%, which resulted from the enhancement in electron injection at quantum dot (QD)/ electron transporting layer (ETL) interface. It was confirmed by the measurement of the depth profile of X‐ray photoelectron spectroscopy (XPS). It indicated that cathode material, aluminum (Al), diffused into ETL material, zinc oxide (ZnO), leading to aluminium zinc oxide (AZO) alloy, Al doped ZnO.